INTERNATIONAL NON-GOVERNMENTAL ORGANIZATIONS AND HUMANITARIAN RESPONSE IN NORTH EAST NIGERIA: UNOCHA IN PERSPECTIVE (2016 - 2022) - ABUBAKAR HASSAN; ADEJOH SUNDAY (International Studies Journal)
The Boko Haram insurgency in North-East(NE) Nigeria continues into its 12th year. The conflict and insecurity have displaced millions of people, devastated agricultural production and other livelihoods, cut off essential services, and caused a crisis of protection. Since 2016, humanitarian organizations have been working in support of the Government of Nigeria to robustly scale up the life-saving support response to population in crisis. International non-governmental organizations (INGOs) are increasingly playing vital role in humanitarian response around the world. This perspective emphasizes that enhanced efforts to address the root cause of conflicts are a priority to addressing humanitarian crises through coordinating activities of state and non-state actors. This study, therefore, assess the role of Office of the Coordination of Humanitarian Affairs (OCHA) in humanitarian response across the North-east Nigeria from 2016 to 2022. The study relied on secondary source of data obtained from OCHA websites. The study adopts the human needs theory as its framework. This theory believes that conflict is a tragic expression of unmet human needs which implies that all actions undertaken by human beings are attempts to satisfy their needs and means of livelihood. The findings of the study highlight the key role of OCHA in humanitarian information management, coordination, advocacy, policy and financing has contributed tremendously to the life-saving programming effort to help the people affected by the Boko Haram conflict in NE Nigeria to recover and regain their dignity. The paper recommends that the humanitarian actors in NE Nigeria should establish robust information database for excellent impact assessment, evidence-based policy and better value for money programming.